2016
DOI: 10.1155/2016/4359415
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Sensor Network with Enhanced Power Efficiency and Embedded Strain Cycle Identification for Fatigue Monitoring of Railway Bridges

Abstract: Wireless sensor networks have been shown to be a cost-effective monitoring tool for many applications on civil structures. Strain cycle monitoring for fatigue life assessment of railway bridges, however, is still a challenge since it is data intensive and requires a reliable operation for several weeks or months. In addition, sensing with electrical resistance strain gauges is expensive in terms of energy consumption. The induced reduction of battery lifetime of sensor nodes increases the maintenance costs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Furthermore, because the detected event is a train that travels to the bridge, there is a significant amount of metal between sentinel nodes and monitoring nodes while the alarming process is on-going. Past field tests experience suggested that passing trains have a significant impact on the link quality between network nodes [17] which could affect the speed and reliability of alarm message delivery. TinyOS 2.x, [20] the operating system for WSNs that was used in this work, provides a built-in mechanism for disseminating small pieces of data (smaller than a single packet payload), which could be used for alarm message delivery.…”
Section: Alarming Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, because the detected event is a train that travels to the bridge, there is a significant amount of metal between sentinel nodes and monitoring nodes while the alarming process is on-going. Past field tests experience suggested that passing trains have a significant impact on the link quality between network nodes [17] which could affect the speed and reliability of alarm message delivery. TinyOS 2.x, [20] the operating system for WSNs that was used in this work, provides a built-in mechanism for disseminating small pieces of data (smaller than a single packet payload), which could be used for alarm message delivery.…”
Section: Alarming Processmentioning
confidence: 99%
“…In case that the threshold was exceeded, the second processing step identifies strain cycles of a record according to the algorithm described in Feltrin, Pepovic, Flouri, and Pietrzak. [17] It searches a data record for consecutive local extremal points (maxima and minima, Figure 9). Because in fatigue assessment methods, the impact of small amplitude cycles below the endurance limit is neglected, while processing the record, the algorithm simultaneously removes cycles that are smaller than a given threshold.…”
Section: Operation Modementioning
confidence: 99%
See 1 more Smart Citation
“…• In 2014, Feltrin et al [4] developed and deployed a custom sensor node for railway bridges to predict fatigue from train traffic. Their custom sensor node was based on the TI MSP430 SoC, and a sub-GHz radio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Key findings were that measurements were validated against wired sensors; ACKs were required to avoid data loss; and various measures including adapting transmit power could be used to reduce power consumption. • In 2014, Feltrin et al [21] developed and deployed a custom sensor node for railway bridges to predict fatigue from train traffic.…”
Section: Related Workmentioning
confidence: 99%